Jurnal Penyuluhan: Motivasi, Kepuasan Kerja dan Kinerja Penyuluh Kehutanan di Kabupaten Cianjur Jawa Barat - Firmansyah, Siti Amanah, Dwi Sadono (PPs ILMU PENYULUHAN PEMBANGUNAN IPB, 2015)
Performance of forestry extension workers would contribute to the achievement of extension goals. The study aims to find performance of forestry extension workers in relations to their profile, motivation and job satisfaction.